Metrological Terms in Croatian Dictionary Heritage - Jakobović, Zvonimir; Boras, Damir (2004)
In the section of the project entitled Croatian Dictionary Heritage old Croatian dictionaries are being researched in relation to the old terminology used in natural and technological sciences of the time: the terminology of metrology has been chosen as experimental expert terminology ; the reason is that old dictionaries are especially rich in metrology concepts and its corresponding terminology ; the reason is also a special importance of metrology for the complete order of human society and its basic activities ; such basic activities are: distribution of goods, trade, paying taxes and other fees, realisation of rights and privileges, land measurement ; it is certain that the metrological terminology is an essential component of basic legal documents, such as donations, charters, land registers, lists and protocols on landed property supervision, as well as on administrative, military and church provinces etc.
Projekt MZOS
ENG